A decision tree to determine fitness to drive in epilepsy: Results of a pilot in two Australian states. (21st May 2019) - Somerville, Ernest R.; ,
Abstract: Objective: Certification by treating physicians of fitness to drive in people with epilepsy creates a conflict of interest that may result in unsafe decisions, damage the doctor‐patient relationship, expose the physician to legal liability and prevent optimal treatment. Ideally, the treating physician should provide objective clinical information to the driver licensing authority (DLA), which then determines fitness or otherwise. However, DLAs in Australia do not employ medical staff and the national standards are complex. Fitness is determined by the treating physician, according to published national standards. The purpose of this study was to determine the feasibility of using a decision tree to determine fitness, according to the Australian standards. Methods: A decision tree was constructed to use clinical data to determine whether a patient met the national standard to drive a private motorcar, failed to meet it or required further assessment. A form was designed to collect the necessary clinical data from the treating physician. A computerized version of the decision tree was then used in a pilot in two Australian states in parallel with the existing certification system. Four hundred thirty‐nine drivers with declared epilepsy and their treating physicians were invited to participate when their annual driver licence review was due. Results: Two hundred fifty‐three (58%) forms were returned. All patients were considered fit to drive by their physician. Seventy‐six percent had not had a seizure for over two years. In 88.1%, there was agreement between the decision tree and treating physician, with 3.6% identified by the decision tree as requiring review. Although considered fit by their physician, 6.3% did not meet the national standard to drive. Significance: The decision tree model is a practical alternative to fitness certification by treating physicians. This Australian pilot can serve as a model for applying objective standards to driving assessments in other jurisdictions, using local driving standards. It has the potential to improve road safety by avoiding the negative effects of certification by treating physicians and can cope with complex standards. It is now in use in two states of Australia.